Analysis of Convergence of Fiscal Variables in Sub-Saharan African Countries (1981-2007): A Stochastic Technique - Olasunkanmi, OSENI Isiaq (Journal of Economics and Behavioral Studies, 2011)
The study examined the analysis of convergence of fiscal variables among Sub-Saharan Africa (SSA) countries for the period 1981-2007. Secondary time-series data were used for the study and analysed using econometric techniques. The results showed that there were convergence in Burkina Faso, Cameroon, Nigeria, Rwanda, Sierra Leone and Uganda while there were divergence in Burundi, Kenya, Mauritius and South Africa. The study concluded that only Burkina Faso, Cameroon, Nigeria, Rwanda, Sierra Leone and Uganda could form Economic and Monetary Union (EMU) as a result of their convergence of Fiscal Variables.